Wearable System for Simultaneous and Noninvasive Detection of ECG and Blood Flow - Méndez-Lira, O. A.; Gutiérrez-Chávez, A.; Cota-Ruiz, J. D.; Díaz-Román, J. D.; Sifuentes-De la Hoya, E.; González-Landaeta, R. E. (Revista Mexicana de Ingenieria Biomedica, 2018)
A wearable system was developed for the simultaneous and non-invasive detection of two signals from cardiac ac-tivity: the ECG and blood flow. Two dry electrodes were used to detect the lead I of the ECG. The detection of blood flow was performed non-invasively using a tunnel-magnetoresistance (TMR) sensor based on the magnetic signa-ture of the blood over a constant magnetic field from a permanent magnet. The electrodes, the TMR sensor and the magnet were mounted on a wristband-type bracelet for the user comfort. The instrumentation developed to detect the ECG and blood flow was designed based on a differential configuration with a common-mode rejection ratio hi-gher than 87 dB at 60 Hz and with a noise voltage in such a way that the cardiac signals presented a signal-to-noise ratio greater than 41 dB, as long as the subject stays still during the measurement. The quality of the signals was enough to extract information from these signals by means of simple to implement algorithms. The proposed sys-tem is an alternative to the wearable systems presented so far, from which it is possible to assess the cardiovascular health of the subject in non-hospital environments.